A study on physical properties of self compaction concrete by using rice husk ash (RHA) in concrete / Wan Mohamad Azizie Wan Azmi - Wan Azmi, Wan Mohamad Azizie (Faculty Architecture, Planninng and Surveying, 2014)
Technology in concrete has been developed in many ways to enhance the quality and properties of concrete. One of the technological advances in improving the quality of concrete is by using self-compaction concrete (SCC). This research was carried out to establish the physical properties of self-compaction concrete by using rice husk ash (RHA) in concrete with mix design of constant water-cement ratio. The main objective of this study is to investigate the properties and strength development SCC by using RHA as cement replacement material. There are four compositions of mixes were prepared and laboratory test was carried out to investigate the properties and the strength development of hardened concrete that using rice husk ash as cement replacement. A total of 36 concrete cube specimens 100 mm x 100 mm x 100 mm were prepared for Slump Test, Water Absorption and compression test at 7, 14 and 28 days. The results for cube tests indicated that sample with 0%, 10% RHA, and 20% RHA, and 30% RHA is the optimum composition for self-compaction concrete. This composition optimizes the use of cement with the performance of hardened concrete.